The OPEC after thirty years - Klaus Matthies (Intereconomics, 1990)
The collapse if OPEC has been prophesied repeatedly since it was first founded in Baghdad in September 1960. Yet in spite of all their differences its members, which now number 13 countries, have so far always managed to establish at least a formal bare minimum of consensus. It may be that recent events have changed all that. Will OPEC's thirtieth birthday prove to be its last?
Keywords: 330; OPEC